Super fraction #1

Algebra Level 3

f ( n ) = 1 + 1 n + 1 n + 1 n + . . . f(n)=1+\frac{1}{n+\frac{1}{n+\frac{1}{n+...}}}

Given that f ( n ) f(n) can be expressed as a n b ± ( n 2 + c ) d 4 d \frac{an-b\pm(n^2+c)^d}{4d} find a + b + c + d a+b+c+d

Extension: Is 0 0 a valid input for n n ?


The answer is 1.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let g ( n ) = f ( n ) 1 g(n) = f(n) - 1 . Then g ( n ) = 1 n + g ( n ) g(n) = \frac{1}{n+g\left(n\right)} . Solving for g ( n ) g(n) :

g ( n ) 2 + n g ( n ) 1 = 0 g\left(n\right)^{2}+ng\left(n\right)-1=0

g ( n ) = n ± n 2 + 4 2 g\left(n\right)=\frac{-n \pm \sqrt{n^{2}+4}}{2}

Substituting g ( n ) = f ( n ) 1 g(n) = f(n) - 1 and solving for f ( n ) f(n) yields:

f ( n ) = n + 2 ± n 2 + 4 2 f\left(n\right)=\frac{-n+2 \pm \sqrt{n^{2}+4}}{2}

Therefore, a = 1 , b = 2 , c = 4 , d = 1 2 \boxed{a = -1, b = -2, c = 4, d = \frac{1}{2}}

Ved Pradhan
Jun 29, 2020

f ( n ) = 1 + 1 n 1 + f ( n ) f(n)=1+\dfrac{1}{n-1+f(n)} f ( n ) ( n 1 + f ( n ) ) = n 1 + f ( n ) + 1 f(n)(n-1+f(n))=n-1+f(n)+1 f ( n ) 2 + ( n 1 ) f ( n ) = n + f ( n ) f(n)^{2}+(n-1)f(n)=n+f(n) f ( n ) 2 + ( n 2 ) f ( n ) n = 0 f(n)^{2}+(n-2)f(n)-n=0 f ( n ) = n + 2 ± ( n 2 4 n + 4 + 4 n ) 1 2 2 f(n)=\dfrac{-n+2\pm(n^{2}-4n+4+4n)^{\frac{1}{2}}}{2} { a = 1 b = 2 c = 4 d = 0.5 \begin{cases} a=-1 \\ b=-2 \\ c=4 \\ d=0.5 \end{cases} a + b + c + d = 1.5 a+b+c+d=\boxed{1.5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...